SOCIO-ECONOMIC FACTORS INFLUENCING PRIMARY SCHOOL DROPOUT AMONG HOUSEHOLDS IN KITUI EAST SUB-COUNTY, KENYA - Kituu, Benjamin Mutua; Odek, Antony Wando (American International Journal of Social Science Research, 2025)
School dropout in Kitui East Sub-County undermines any vision for education equity despite national reforms like Free Primary Education and the 100% transition. This study explored how household-level factors affect school retention, specifically parents’ financial status, education level, and involvement. It is underpinned by Social Capital, Human Capital, and Ecological Systems theories and used a mixed-methodology design. The study employed cluster, random, and purposive sampling to obtain a sample of households from a population of 17,497 and sampled 377 households for data collection via surveys and interviews. Quantitative data were analyzed using descriptive statistics, Chi-square tests of associations, and logistic regression to determine the impact of covariates on school retention or dropout, and qualitative data analyzed thematically. The study findings show that 48.7% of households could not afford schooling, and availability of an income source was strongly associated with affordability (χ² = 15.29, p = 0.0016). Parents’ inability to afford schooling resulted in dropout odds being 3.2 times greater for those cases. Parental level of education reduced the risk of dropout for each emerging level of education while use of reading sensitization materials resulted in lower odds of dropouts. The study concludes that income security, parents’ literacy, and parents’ active role in literacy, clearly emerged as major influences on school continuity within rural households. The study recommends for flexible payment schedules for school levies, school-based parent sensitization meetings/forums for parents to attend, and access to adult literacy programs locally as the study report concludes.